Community Psychology and Transformative Policy Change in the Neo‐liberal Era. Issue 3 (23rd July 2013) - Nelson, Geoffrey
Abstract: I present ideas about how community psychologists, as researcher‐activists, can influence public policy. I begin by describing the current neo‐liberal era, noting the immense obstacles it poses to progressive policy change. Next I contrast two approaches to understanding policy formation, evidence‐based policy and discursive policy analysis, and argue that transformative policy change can benefit from both approaches. I then propose three types of policy outcomes that community psychology research and activism should aim to promote: (a) shaping problem definition, (b) controlling channels for debate and participation, and (c) allocating resources. I use examples from community psychologists' involvement in policy, mostly in Canada, to illustrate how such policy change can be both achieved and constrained. I conclude by discussing implications for theory and practice related to policy change.